2017
DOI: 10.21608/mvmj.2017.127611
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Lincomycin and Spectinomycin in Rats

Abstract: This study was performed to investigate the adverse effects of lincomycin (given orally at 500 mg/kg daily for 21 days) and spectinomycin (given S.C at 250 mg/kg daily for 30 days) on 24 apparently clinically healthy adult male albino rats (175 -250 gm). Blood, serum and tissues (Liver, kidney and testis) samples were collected for hematological, biochemical and histopathological for investigation. The obtained results revealed that, lincomycin and spectinomycin treated groups showed a significant decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
2
1
0
Order By: Relevance
“…Possibly the difference observed between our results is due to the difference in drug concentration and days of treatment, where in the present study, the highest dose administered was 40mg/kg -1 for 8 days. Studies evaluating oral administration of Lincomycin in rats (AMER et al, 2017) and in beagles (GRAY et al, 1964) observed a transient increase in ALT and AST, with their values returning to baseline levels, corroborating the findings of our study with tilapias. This increase in enzymatic activity can be attributed to changes in the permeability or cytotoxicity of hepatocytes in the drug metabolic degradation, leading to their release from the cytoplasm into the bloodstream after damage or rupture of the plasma membrane (OYENIRAN et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Possibly the difference observed between our results is due to the difference in drug concentration and days of treatment, where in the present study, the highest dose administered was 40mg/kg -1 for 8 days. Studies evaluating oral administration of Lincomycin in rats (AMER et al, 2017) and in beagles (GRAY et al, 1964) observed a transient increase in ALT and AST, with their values returning to baseline levels, corroborating the findings of our study with tilapias. This increase in enzymatic activity can be attributed to changes in the permeability or cytotoxicity of hepatocytes in the drug metabolic degradation, leading to their release from the cytoplasm into the bloodstream after damage or rupture of the plasma membrane (OYENIRAN et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In the study, there was a transient increase in triglycerides and cholesterol at dose of 40mg, possibly due to impaired liver function, and their values returned to normal levels within reference intervals previously recorded for tilapia under normal health conditions (MAUEL et al, 2007;HRUBEC et al, 2000). A study evaluating the oral administration of lincomycin in rats (AMER et al, 2017) also observed the same response profile.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation